Reaction of Diphenylpicrylhydrazyl (Dpph) with Antioxidants in Presence of Poly(?-Caprolactone)/Poly(N-Vinyl-2-Pyrrolidone) Block Copolymer Nanoaggregates - Lissi-Gervaso, E (2011)
The reaction of antioxidants with 2,2-diphenyl-l-picrylhydrazyl (DPPH) has been studied employing both, ethanol and nano aggregates biodegradable block copolymers (BBC) in aqueous solution, as reaction media. Gallate derivatives with different chain lengths (gallic acid, methyl, propyl and octyl gallate) were used as antioxidants model, and BBC containing a central section of poly-?-caprolactone (PCL) and three arms of poly-vinylpirrolidone (PVP) were used to originate nano aggregates in aqueous solution. The course of the reaction was followed by the changes of the DPPH absorption band at 517 nm. In ethanol, using an excess of antioxidants, DPPH was consumed completely by all gallate derivatives. Nevertheless, when the same reaction was carried out in aqueous nano aggregates of BBC, only a partial consumption of DPPH was observed, suggesting the occurrence of a complex reaction mechanism. Copyright © 2011 American Scientific Publishers All rights reserved.